Measuring vulnerability to natural hazards towards disaster resilient societies - Birkmann, Jörn (United Nations University Press, 2006)
A seemingly non-stop series of disasters has shown that societies worldwide seem unprepared for the threats posed by natural hazards. The tragic impacts of these events drew short-term attention from policy makers, the media and the general public, but their response was too late to prevent serious harm. Societies need to measure their vulnerabilities in advance, and make adequate provisions. This publication presents a broad range of current approaches to measuring vulnerability and contains concrete experiences and examples from Africa, Asia, the Americas and Europe to illustrate the theoretical analyses.--Publisher's description.